Evaluation of the haematological parameters in Piaractus mesopotamicus Holmberg (Osteichthyes, Characidae) with Argulus sp. (Crustacea, Branchiura) infestation and treatment with organophosphate - Tavares-Dias, Marcos [UNESP]; Martins, Maurício Laterça [UNESP]; Kronka, Sérgio do Nascimento [UNESP] (Sociedade Brasileira de Zoologia, 1999)
Haematological parameters as erythrocytes, leukocytes and plasma glucose in Piaractus mesopotamicus Holmberg, 1887 were analyzed. Fish were parasitized with Argulus sp. (Crustacea, Branchiura) and treated with 0.4 mg of thriclorphon 500/L water. The effects of parasitism and the action of the treatment were evaluated. Parasitized fish showed greater number of monocytes (P>0.05) and special granulocitic cells (P<0.01) in the peripheric blood than the unparasitized (control) fish. Parasitized fish showed lower number of thrombocytes (P>0.05). Organophosphate treatment presented significantly reduction (P>0.05) in red blood cells (RBC) and hemoglobin.
Keywords: Piaractus mesopotamicus; Argulus; parasitism; haemathology